Intelligence and language outcomes in school-aged children who are HIV-exposed, uninfected: the role of sex, perinatal risk factors, and socioeconomic status - Kahnami, Leila; Smith, Mary Lou; Bitnun, Ari; Brophy, Jason; Sled, John G.; Miller, Elka; Bowes, Jennifer; Hurtubise, Mariève; Serghides, Lena; Young, Julia M. (Frontiers in Pediatrics, 2025)
BackgroundChildren who are HIV-exposed uninfected (CHEU) are at increased risk for neurodevelopmental impairments. Most studies report on neurodevelopmental outcomes in the first 2 years of life, with limited data available for school-aged CHEU. This interim study examined the intellectual and language outcomes in school-aged CHEU compared to children who are HIV-unexposed uninfected (CHUU).SettingCHEU and CHUU aged 6–10 years recruited at two sites in Ontario, Canada.MethodsIntellectual and language abilities were measured using the WISC-V and CELF-5. Generalized linear models investigated associations of HEU-status with each neurodevelopmental outcome. An interaction term with sex was included to assess sex-specific effects. Gestational age, being small for gestational age (SGA), and household income were investigated as covariates.Results65 CHEU (35 female, median age 9.00 years) and 42 CHUU (18 female, 8.96 years) were included. HEU-status was associated with significantly lower working memory and expressive language scores. In males, HEU-status was associated with lower scores on working memory, processing speed, overall intelligence, core, and expressive language abilities. No significant differences were observed in females by HEU-status. Household income was associated with all measures of intelligence and language. Lower working memory scores persisted in male CHEU after adjusting for covariates.ConclusionMale CHEU and those with lower household income were the most vulnerable to cognitive and language deficits. Working memory deficits in CHEU indicates a specific cognitive vulnerability due to HEU exposure status. Our findings highlight the need for early interventions, including ensuring financial security and close neuropsychological follow-up.